2021
DOI: 10.1371/journal.pgph.0000006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of attrition among patients receiving ART in eastern Zimbabwe before, and after the introduction of universal ‘treat-all’ policies: A competing risk analysis

Abstract: As HIV treatment is expanded, attention is focused on minimizing attrition from care. We evaluated the impact of treat-all policies on the incidence and determinants of attrition amongst clients receiving ART in eastern Zimbabwe. Data were retrospectively collected from the medical records of adult patients (aged≥18 years) enrolled into care from July 2015 to June 2016—pre-treat-all era, and July 2016 to June 2017—treat-all era, selected from 12 purposively sampled health facilities. Attrition was defined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This figure is higher than the previous study undertaken in Ethiopia prior to the commencement of the test and treat era [ 22 ]. On the other hand, it is consistent with the previous research findings conducted in Zimbabwe following UTT [ 14 , 16 ]. The likely explanation for this agreement could be the comparable socioeconomic status and HIV management protocol of the two countries, which indirectly increases the risk of early mortality and loss from ART treatment [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This figure is higher than the previous study undertaken in Ethiopia prior to the commencement of the test and treat era [ 22 ]. On the other hand, it is consistent with the previous research findings conducted in Zimbabwe following UTT [ 14 , 16 ]. The likely explanation for this agreement could be the comparable socioeconomic status and HIV management protocol of the two countries, which indirectly increases the risk of early mortality and loss from ART treatment [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, research in Zimbabwe that looked at predictors of attrition before and after the “test and treat era” found that patients who enrolled in ART after the test and treat era had a 73% higher risk of attrition than their peers [ 14 ]. Additionally, Studies in Nigeria [ 15 ], Uganda [ 2 , 14 ], Zimbabwe [ 16 ]and South Africa [ 17 ] revealed that rapid initiation of ART increases the incidence of attrition through enhancing early LTFU. In Nigeria and South Africa, nearly 34% and 33% of patients who commenced into ART under this era were immediately loss from their regular care [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a growing number of reports on increasing trends in attrition during ART suggest that universal ART eligibility may attract more patients with low motivation to adhere. They would have likely dropped out of pre-ART care had eligibility been determined on the basis of immunological/clinical criteria [ 16 18 ]. Therefore, introducing MI following HIV diagnosis would be a promising strategy to motivate ART initiation and encourage adherence behaviours in PWID during early ART—the critical period in which the risk of mortality and treatment discontinuation peaks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tlhajoane et al provided data for a few patients who had 12 months follow-up, while Makurumidze et al and Mayasi et al con rmed that none of the included participants had less than 12 months follow up [18,19,25]. None of the studies reported pre-ART attrition.…”
mentioning
confidence: 99%